Attendance of Pop and Classical Music Concerts among the Hungarian Youth - Péter, Csaba (Central European Journal of Educational Research, 2021)
In this paper we wanted to give a comprehensive picture of capital theories from a theoretical point of view, looking at it from several angles. In our empirical study, we analyzed the Hungarian Youth Research 2016 database, which was recruited Hungarian youth aged 15-29. The study was conducted with several variables in mind, mapping the influence they have on the attendance of classical and pop music concerts. We took into account the gender, age, place of residence of the respondents, the highest level of education and looked at the frequency of the concert attendance by counties and regions. Our results show that many variables influence the frequency of attendance at concerts by both genres.